MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MENGGUNAKAN PENDEKATAN PAKEM SISWA KELAS 1 SDN 15 LIMBOTO BARAT - Yuliyanti Ismail; Abd. Hamid Isa; Yulanti Mooduto (Jurnal Ilmu Pendidikan UMGo, 2025)
: This research aims to determine how the PAKEM approach can improve the beginning reading ability of grade 1 students at SDN 15 Limboto Barat. This is motivated by the low ability of students in the beginning reading. This study uses the method of classroom action research (CAR) from Kemis & Mc Taggart, carried out with two cycles. . The research subjects were 20 students, with 11 male students and nine female students. Data collection techniques in this study were observation, tests, interviews, and documentation. The research instruments used were teacher activity instruments, student activities in the form of a checklist, and a sheet of beginning reading skills, including Indicators of the ability to pronounce, spell, pronounce and understand. The results showed that students beginning reading ability in the initial observation of 18 people, or 90% of students, were unable to read the beginning, according to KKM ≥ 75. After the action in cycle I, nine students, or 45%, were able and 11 students, or 55%, were unable. Furthermore, 18 students, or 90%, were able to in cycle II, and two students, or 10%, were unable. Remedial and parental guidance is given to students who cannot do so. Thus the action hypothesis, which states that "if the teacher uses the PAKEM approach, the beginning reading ability of grade I students of SDN 15 Limboto Barat will improve, is accepted".